Conception of implementing a Service Oriented Architecture (SOA) in a legacy environment - Erik Froelian; Gregor Sandhaus (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2012)
This research paper discusses how existing IT-infrastructure can be enhanced with Service-Oriented Architectures (SOA). Legacy systems are known for being quite limited in terms of interfaces, standardization and interoperability with other software systems. At the same time legacy systems provide core data and functionality to the enterprise that has deployed this system. Therefore a SOA might be a suitable approach to provide legacy data and functionality to modern systems like web applications. This paper describes SOA and its design and technical principles as well as legacy systems and how both can be linked to meet nowadays requirements in the software development process. Three case studies are described to point out the capabilities and limitations of SOA and a process model is suggested for its deployment.
Keywords: 650; Unternehmensarchitektur